The Effect of Fertilization Systems and Tillage Depths on Soil Content of Organic Matter and Some Mineral Nutrients - Abdelaziz , Mohammad Ali; Grad, Sumer Ali; Ali, Bsam Nahet (Latakia University Journal -Biological Sciences Series, 2013)
The reasearch was carried out during 2009 – 2010 in Al – Hasaka – Amoda - to study the effect of cattle manure at the rat of 30 ton / ha , and four organic green manure ( Lentil, Vetch, Faba bean and Barely) on soil content of organic matter and some mineral elements compared with chemical fertilizer 400 kg / ha urea , 83 kg / ha P2O5 and 25 kg / ha K2O . The manure significantly increased organic matter , phosphorus and potassium concentrations compared with other fertilizers ( chemical and green fertilizers ) . All green fertilizers ( Lentil , Vetch , Faba bean and Barely ) significantly increased organic matter , nitrogen and potassium concentration compared with the control without using any fertilizer , the tillage depth ( 0 – 10 ) cm significantly increased soil content of organic matter and nitrogen compared with deeper tillage ( 25 – 30 ) cm during the two seasons .